Peran Al-Asy'ari dan Al-Maturidi dalam Melestarikan Aqidah Ahlussunah wal Jamaah - Yanto Maulana Restu; Siti Munawaroh; Silvi Yumnita Maulani; Tsamrotul Amaliah; Abdul Aziz (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The development of Islamic theology has been closely intertwined with ongoing debates between rational and textual approaches that emerged alongside social and intellectual transformations within the Muslim community. In this context, Imam Abu al-Hasan al-Ash‘ari and Imam Abu Mansur al-Maturidi played a crucial role in preserving and strengthening the creed of Ahl al-Sunnah wa al-Jama‘ah as the mainstream theological framework of Islam. This study is motivated by the need for a comprehensive understanding of their contributions in responding to extreme theological trends, either those that excessively prioritized reason or those that entirely rejected rational inquiry. The purpose of this research is to analyze the roles of Al-Ash‘ari and Al-Maturidi in formulating a moderate and balanced theological foundation for Ahl al-Sunnah wa al-Jama‘ah. This research employs a qualitative descriptive method through library research, involving a critical review of classical theological works and relevant scholarly literature. The findings indicate that Al-Ash‘ari and Al-Maturidi successfully constructed a theological framework that integrates the authority of revelation with the function of reason in a proportional manner. Their approaches preserved the purity of Islamic creed while allowing constructive engagement with intellectual developments. The study concludes that the theological contributions of Al-Ash‘ari and Al-Maturidi have significant implications for strengthening religious moderation and ensuring the continuity of Ahl al-Sunnah wa al-Jama‘ah creed amid contemporary intellectual challenges. This framework remains relevant as a theological foundation for Muslims in navigating modern pluralism and global ideological dynamics.   Keywords: Ahlussunnah wal Jamaah, Al-Asy’ari, Al-Maturidi, Islamic Theology, Religious Moderation